CHILD IMMIGRANT POST-MIGRATION MENTAL HEALTH: A QUALITATIVE INQUIRY INTO CAREGIVERS’ PERSPECTIVES - Fakhari, Nahal; McIsaac, Jessie-Lee D.; Spencer, Rebecca (International Journal of Child, Youth and Family Studies, 2023)
Immigrant families and their children experience isolation after migration to Canada. Inadequate income, unemployment, and underemployment have all been identified as primary challenges to the mental health of immigrant families. This study qualitatively explored the perceptions of six Middle Eastern immigrant caregivers regarding their children’s post-migration mental health. The research was situated in the constructivist paradigm, and qualitative descriptive design was used to explore participant experiences. Interviews were conducted in English with three Farsi-speaking and three Arabic-speaking caregivers. Reflexive thematic analysis was performed. Three themes were developed: (a) parents feel their children are isolated and lonely; (b) caregivers’ limited access to resources impacts their children’s mental health; and (c) community connections enhance families’ mental health. Findings suggest children’s experiences with family separation and exposure to racism contributed to children’s loneliness. Children’s isolation was exacerbated by caregivers’ limited access to resources to support their children’s transition into Canada. Caregivers identified social support as an asset to their families’ mental health. This research highlights the importance of culturally responsive health, employment, and education policies, together with programs to provide resources for immigrant families to support their children’s mental health after migration.